If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying h(-3) = 3x + -3 Reorder the terms for easier multiplication: -3h = 3x + -3 Reorder the terms: -3h = -3 + 3x Solving -3h = -3 + 3x Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Divide each side by '-3'. h = 1 + -1x Simplifying h = 1 + -1x
| =11+0.9(y-10) | | 25+x=78 | | 2x+7=3x-(6x-2) | | 2(p+5)-3p=14 | | X+X+1(X+2)=160 | | 4x+-3x+-5x= | | -5y+3-4y=2 | | 2.14-0.3x=2.24 | | 1/2=x1/4 | | 75000=x(x+3) | | 5(x+4)=3[x-(4-x)] | | 15x+30=15x-90 | | -2.9=f+4.3 | | 2x-12y+5=0 | | sinx+14.87cosx=1.5 | | 0.5x+0.08=0.13 | | 3(g-2)+2=5g-7-2g | | 12x-(3x-9)=27 | | (x-2)(x-2)(x+3i)(x-3i)=0 | | 175000=x(x+3) | | 7x+10000=5x+14000 | | 7x+10000=10x+6000 | | f(-4)=8 | | (-5(x=6)/3)=10 | | 8750=x(x+3) | | 2n+3.75=7n | | 2s-13=27 | | 3(2p+5)-4(p+3)= | | 1750=x*(x+3) | | 2.3x+5.6=3.4 | | 6a+9=23 | | 7x-10+2x=5-x |